The Role and Training of Hospital Paediatric Nurses in Papua New Guinea - John Biddulph (Paediatrica Indonesiana, 1976)
Demands for health services are increasing in all countries of the world. Both affluent and less affluent countries are starting to realise to the importance of nurse practitioners to enable comprehensive health services to be made available to more people at cheaper cost. The training programme for hospital paediatric nurses in Papua New Guinea has been designed to allow them to carry out effectively their future role of taking responsibility for the screening, diagnosis and initial treatment of sick children pending the availability of a doctor. The nurses receive practical on the job training by rotating through specific areas during the one year post basic course in paediatric nursing. The areas are acute paediatric ward, gastroenteritis ward, special care nursery, paediatric outpatients, nutrition rehabilitation unit and MCH clinics. The nurses learn to diagnose the common acute paediatric illnesses. They learn standardised management regimens for each of these common childhood illnesses. They also learn how to carry out the practical procedures required to allow them to diagnose and treat these illnesses, and become skilled in doing such procedures as lumbar punctures and intravenous rehydration.